THE ROLE OF AFFECTIVE COMMITMENT IN MEDIATING THE EFFECT OF EMPLOYEE COMPETENCY, TRAINING AND ORGANIZATIONAL CULTURE ON EMPLOYEE PERFORMANCE (EMPIRICAL STUDY AT THE CLASS I AGRICULTURE QUARANTINE SEMARANG) - Lilik Setiawan; Didi Hermanto; Sugeng Bowo Handayani (LPPM ITB AAS INDONESIA (d.h STIE AAS Surakarta), 2021)
The purpose of this study was to analyze the role of affective commitment in mediating the influence of employee competencies, training, organizational culture on employee performance. The population in this study were employees of the Class 1 Agricultural Quarantine Semarang, which numbered 100 employees. The sampling method uses the census method. The data were analyzed using Partial Least Square. This study shows that employee competency, training, and organizational culture have a significant positive effect on affective commitment. Affective commitment, employee competency, and organizational culture have a significant positive effect on employee performance. Training does not affect employee performance. Affective commitment can mediate in full (complete) the influence of employee competency, training, organizational culture on employee performance. Keywords: employee competency, training, organizational culture, affective commitment, employee performance.